THE ROLE OF PDGF AND TSP-1 IN THE DEVELOPMENT OF SYSTEMIC SCLERODERMA - Abdakimova Baxtigul Ilhomiddin qizi (Web of Journals Publishing, 2025)
Systemic scleroderma (SSc), also called systemic sclerosis, is a chronic autoimmune disease. It causes: - Thickening and hardening of the skin - Damage to small blood vessels - Fibrosis of internal organs (like lungs, heart, kidneys)
Keywords: Systemic scleroderma, PDGF, TSP-1, fibrosis, angiogenesis, vascular damage, autoimmune disease, TGF-beta, fibroblasts, treatment.